Inhibition of Apoptotic Pathways Improves DNA Integrity but Not Developmental Competence of Domestic Cat Immature Vitrified Oocytes - Colombo, Martina; Zahmel, Jennifer; Jänsch, Stefanie; Jewgenow, Katarina; Luvoni, Gaia Cecilia (Frontiers in Veterinary Science, 2020)
Being a model for endangered wild felids, cryopreservation protocols for domestic cat oocytes are under continuous development. Immature vitrified oocytes (VOs) are a valuable resource for fertility preservation programs, but they often degenerate after warming and their in vitro development is poor. Since the exact mechanisms are not clear, this study assessed whether vitrification might trigger two apoptotic markers (DNA fragmentation and caspase activity, Experiment I) and the effects of a chemical inhibitor (i.e. the pan-caspase inhibitor Z-VAD-FMK) on the same markers (Experiment II) and on VOs in vitro development (Experiment III). The overarching aim was to check whether apoptosis inhibition might be a strategy to improve cat oocytes cryotolerance. In Experiment I, vitrification induced DNA fragmentation and increased caspase activity in VOs incubated for 24 h after warming (DNA fragmentation: 59.38%; caspase activity: 414.6±326.8) compared to a fresh control (9.68%; 199.6±178.3; p=0.02). In Experiment II, the addition of Z-VAD-FMK to vitrification-warming and incubation media decreased DNA fragmentation and caspase activity (8.82%; 243.7±106.9) compared to control (untreated) VOs (69.44%; 434.5±248.3; p<0.001). In Experiment III, Z-VAD-FMK brought maturation rates of treated VOs close to those of fresh oocytes (53.13% and 65.38%, respectively, p=0.057), but there were no differences in VOs embryo development (cleavage rates; Z-VAD-FMK-treated VOs: 34.38%; control VOs: 31.78%; p=0.69). In summary, vitrification increased apoptotic markers in cat VOs, and while Z-VAD-FMK was able to hinder DNA damage and caspase activity, its addition was not determinant for embryo development. To make the best use of VOs, other oocyte in vitro maturation and embryo culture strategies, such as the addition of other inhibitors or their prolonged use, should be investigated.